Analysis of sustainable pastureland farming in tropics of Deccan Plateau - BIRADAR, NAGARATNA; KUMAR, ANIL; NATARAJAN, S; CHANDRA, AMARESH; TRIVEDI, B K (The Indian Journal of Animal Sciences, 2012)
A study was conducted by an interdisciplinary team covering pasturelands of 9 blocks of Coimbatore, Erode and Karur districts of Tamilnadu, together referred as Kangaym grasslands. Survey of grasslands, laboratory analysis of grass species, seed bank analysis, market study, stakeholder interviews, secondary and primary data collection were the methods employed. Aristida setacea had the highest importance value index (126.9) in species composition followed by Cenchrus ciliaris (49.2). Contribution of grasses to the total dry matter production was 82.50% and that of legumes was 12.42% with an average production of 1.61 t/ha/year. Acacia leucocephala was the most widely planted tree species with an average density of 358.42 plants/ha with DBH of 7.16±1.13 cm. Among the 10 C.ciliaris accessions, the maximum similarity obtained was 89% between Cenchrus-6 with Cenchrus-4 and 2 major clusters were indicated by dendrogram. Cenchrus spp. dominated the seed bank composition (72.7%). Majority of the farmers (65%) owned sheep. On an average, respondent graze animal for about 6.2 months in the paddocks that contributed more than 80% to its total diet. Balsamodendron berryi was the most commonly used live fence for the paddocks. One-fifth of the respondents reported that livestock contribution to their total farm income was between 75 and 99%. The average family size was 1.55 (G-1), 2.15 (G-2) and 2.4 (G-3) helping them to defer land fragmentation and maintain the big land size (average 10.9 ha).